Investigation on the interface resistance of Si/GaAs heterojunctions fabricated by surface-activated bonding. (9th February 2015) - Liang, Jianbo; Chai, Li; Nishida, Shota; Morimoto, Masashi; Shigekawa, Naoteru
Abstract: The electrical properties of p-GaAs/n + -Si, p + -Si/n-GaAs, p + -GaAs/n + -Si, p + -Si/n + -GaAs, n + -Si/n + -GaAs, and p + -Si/p + -GaAs junctions fabricated by surface-activated bonding (SAB) were investigated. An amorphous layer with a thickness of 3 nm was found across the bonding interface without annealing. The current–voltage ( I – V ) characteristics of p + -GaAs/n + -Si, p + -Si/n + -GaAs, n + -Si/n + -GaAs, and p + -Si/p + -GaAs junctions showed excellent linearity. The interface resistance of n + -Si/n + -GaAs junctions was found to be 0.112 Ω·cm 2, which is the smallest value observed in all the samples. The resistance decreased with increasing annealing temperature and decreased to 0.074 Ω·cm 2 after the junction annealing at 400 °C. These results demonstrate that n + -Si/n + -GaAs junctions are suitable for the connection of subcells in the fabrication of tandem solar cells.